A simplified model design of MMC-HVDC transmission system for steady state and transient stability analyses - Marwan Rosyadi; Atsushi Umemura; Rion Takahashi; Junji Tamura; Takamori Uchiumi; Masanori Mori; Hiroki Miyata (Institute of Advanced Engineering and Science, 2023)
A simplified model of a modular multilevel converter (MMC) implemented on a high voltage direct current (HVDC) transmission system is presented in this study for the analyses of steady-state and transient stabilities. The simplified model design’s goal is to reduce the complicated modeling of the MMC circuit as well as the simulation time of the analysis. The validity of the model design has been examined using the PSCAD/EMTDC simulation program, where the simulation outcomes of the detailed model and the simplified model are contrasted. It has been established that the simplified model is accurate enough and that simulation time can be substantially decreased. It is concluded that the suggested model design is very significant as a simplified model for analyzing the steady state and transient stabilities of MMC-HVDC transmission system.